2021
DOI: 10.1177/23743735211065267
|View full text |Cite
|
Sign up to set email alerts
|

Care Experiences of Older People in the Emergency Department: A Concurrent Mixed-Methods Study

Abstract: The growing population of older people has increased demand to meet their complex healthcare needs, including in emergency departments (EDs). This study explored the experiences of people aged 65+ in Irish EDs, involving secondary analysis of quantitative and qualitative data from the 2019 National Inpatient Experience Survey (NIES). Experiences in the ED and overall hospital experiences were dichotomized as poor to fair or good to very good. Logistic regression was used to model quantitative data. Free text c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The findings reported from this study are consistent with previous research on the experiences of emergency care for older people which emphasise the importance of information and communication, staff attitudes, waiting times and physical/environmental needs in shaping those experiences 2–4 15–18. These aspects of care have also been identified as instrumental in determining the experiences of adult patients generally in the ED 19–21.…”
Section: Discussionsupporting
confidence: 88%
“…The findings reported from this study are consistent with previous research on the experiences of emergency care for older people which emphasise the importance of information and communication, staff attitudes, waiting times and physical/environmental needs in shaping those experiences 2–4 15–18. These aspects of care have also been identified as instrumental in determining the experiences of adult patients generally in the ED 19–21.…”
Section: Discussionsupporting
confidence: 88%
“…However, participants reported that crowding and corridor care were commonly encountered and presented barriers to achieving the desired standards of care. Such concerns are likely to be well-founded, with the effect of ED crowding on mortality and patient experience being well documented in the literature [4,28].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding vulnerabilities in patient experience may also be used to drive meaningful improvements in care [2]. The existing literature places emphasis on the importance of communication, managing wait times and providing a 'frailty-friendly' environment [3,4]. A meta-synthesis of patient experience in the emergency department (ED) proposes a needs-based framework for optimising patient experience, focusing on communication, care, waiting, physical, and environmental needs [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to projections, the percentage of people 60 years and older will rise from 13% in 2010 to 33% in 2040, 1 which causes issues in the demand for health care. 2 Previous studies have shown that 10-26% of older adults have experienced emergency department (ED) visits, 3 8.2% have visited the ED more than five times a year, and individuals over dyspnea from COPD at a large public hospital in the deep south of Thailand in the five years since 2016 gradually increased. 6 Approximately a third of patients with acute exacerbation chronic obstructive pulmonary disease (AECOPD) returned to the ED within 30 days of discharge, similar to other countries.…”
Section: Introductionmentioning
confidence: 99%